Associations between neighborhood environment and sense of community belonging in urban China: Examining mediation effects of neighborly interactions and community satisfaction - Yang Du; Huaxiong Jiang; Zhuo Huang; Haoran Yang; Haoran Yang (Frontiers Media S.A., 2023)
IntroductionImproving sense of community belonging (SCB) would help people live longer, happier lives. Although the importance of neighborhood environment on SCB is stressed in the literature, few studies have paid attention to perceived environment, as well as consider mediation effects such as neighborhood social interactions and place satisfaction.MethodsRelied on a sample of 1051 respondents in Shanghai in 2018, this study investigates the associations between both objective and perceived neighborhood environment attributes and SCB in urban China, mediated by neighborly interactions and community satisfaction using structural equation modeling.ResultsThe results suggest that the influence of perceived neighborhood environment on SCB is more prominent than that of objective neighborhood environment. In detail, perceived pedestrian facilities and perceived leisure facilities are vital to SCB, while among objective neighborhood environmental elements, the influence of land use entropy, park density and street greenery are significant. Then, neighborhood environmental attributes can influence SCB by affecting neighborly interactions and community satisfaction. We also identify gender differences in the effects of neighborhood environment upon SCB.DiscussionGiven increasing awareness of the connection, neighborhood environment may prove to be valuable assets to improve individuals' psychosocial constructs such as SCB.